Molecular dynamics simulation and experimental research on the oxidation reaction of methyl linoleate at low oxygen and high temperature. (1st December 2021) - Sui, Meng; Li, Fashe; Wang, Shuang; Wang, Hua
Graphical abstract: The TG-FTIR-MS combined system analyzed the main gas products of methyl linoleate pyrolysis/high temperature oxidation. Through experiments and ReaxFF-MD calculations, the researchers obtained the main reaction path of the pyrolysis reaction of methyl linoleate and the evolution of double unsaturated bonds. Highlights: TG-FTIR-MS analyzed the main products of pyrolysis of methyl linoleate. Obtained the main reaction path of pyrolysis of methyl linoleate. The evolution of the double unsaturated bond of methyl linoleate is analyzed. Abstract: The pyrolysis and low-oxygen high-temperature oxidation process of methyl linoleate containing two unsaturated double bonds were analyzed by kinetic analysis, density functional theory calculation and ReaxFF-MD considering it as a substitute for biodiesel. The combined system of TG-FTIR-MS was used to analyze the escape characteristics of multi-component gas product during the pyrolysis as well as high-temperature oxidation of methyl linoleate under low-oxygen. The ReaxFF-MD molecular dynamics method was used to analyze the effect of initial reaction path of the thermal decomposition of methyl linoleate and the oxygen content on the oxidation reaction products. The results show that the pyrolysis of methyl linoleate has reaction activation energy of 58.2 kJ/mol, while, for the high-temperature oxidation process under low oxygen, it is 58.79 kJ/mol. The main gaseous products are CO2, CH4, CO/C2 H4, H2 O and products containing C–H, C–O, CO and other functional groups. Through DFT calculations and ReaxFF-MD, we found that breaking of C–O bond leading to the formation of smaller CH3 radical and decarboxylation to form CO2 constitute the initiation mechanism for the pyrolysis of methyl linoleate pyrolysis and high-temperature oxidation in presence of low oxygen. The double bond of methyl linoleate is prone to generate C7 H10 intermediates with higher carbon content during the pyrolysis process. At the same time, through simulation, we found that oxygen and fuel are mixed as soon as possible at the beginning of the combustion of methyl linoleate which helps to reduce the production of C2 products from the pyrolysis of methyl linoleate.